2019
DOI: 10.3892/mmr.2019.10055
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 6A gene silencing suppresses cell invasion and metastasis of nasopharyngeal carcinoma via the β‑catenin cascade

Abstract: Nasopharyngeal carcinoma (NPC) is a type of head and neck cancer. This study aimed to study the mechanisms of ectopic keratin 6A (KRT6A) in NPC. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting were performed to detect KRT6A levels in NPC cell lines (C666-1, 5-8F and SUNE-1) and a nasopharyngeal epithelial cell line (NP69, as a control). After SUNE-1 NPC cells had been silenced by KRT6A, cell viability, metastasis and invasion were determined using Cell Counting Kit-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
3
21
1
Order By: Relevance
“…KRT6A and KRT6B both play important roles in the collective migration of keratinocytes 36 . Previous studies revealed that KRT6A silencing can suppress cell invasion and metastasis of nasopharyngeal carcinoma 37 . KRT6C was found to be closely related to the prognosis and metastasis of lung adenocarcinoma 38 .…”
Section: Discussionmentioning
confidence: 97%
“…KRT6A and KRT6B both play important roles in the collective migration of keratinocytes 36 . Previous studies revealed that KRT6A silencing can suppress cell invasion and metastasis of nasopharyngeal carcinoma 37 . KRT6C was found to be closely related to the prognosis and metastasis of lung adenocarcinoma 38 .…”
Section: Discussionmentioning
confidence: 97%
“…By overlapping the DEGs between the M0-low group and the M0-high group in TCGA with the DEGs between ANT and PDAC, we acquired the potential regulatory genes of TAMs, IAPP, and KRT6A. KRT6A is related to cell invasion and metastasis of nasopharyngeal carcinoma via the β-catenin cascade [ 36 ]. The KRT6A-positive subset of mammary epithelial cells can be induced to form cancer by ErbB2 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nontargeting small interfering RNA (siRNA) 5 0 -CCTAAGGTTAAGTCGCC CTCGCTC-3 0 was used as a negative control, for KRT6A siRNA knockdown experiments the si-RNA targeting sequence, 5 0 -CCAGCAGGAAGAGCUAUA-3 0 was introduced. 6 Transfection efficiency was evaluated by using quantitative reverse transcription PCR (qRT-PCR) and Western blot 48 hours after transfection.…”
Section: Data Sourcesmentioning
confidence: 99%
“…13, which encodes the cytokeratin 6A protein. Keratin 6A is a family member of type II keratin proteins, biologically KRT6A could lead to epidermalization of squamous epithelium, 6,7 and KRT6A plays an important role in EMT in nasopharyngeal carcinoma, 6 KRT6A mutation plays an important role in pachyonychia congenita and could serve as a diagnosis marker. [7][8][9] In present study, the in vitro KRT6A silencing model was constructed to investigate the biological role of KRT6A.…”
Section: Introductionmentioning
confidence: 99%